2008
DOI: 10.1148/radiol.2483072093
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Nephrogenic Systemic Fibrosis: Evaluation of Gadolinium Chelate Contrast Agents at Four American Universities

Abstract: The benchmark incidence of NSF was much greater at the two centers where gadodiamide was used than at the two centers where gadopentetate dimeglumine was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(117 citation statements)
references
References 26 publications
3
110
0
4
Order By: Relevance
“…In vivo major differences between the different GBCAs with regard to short-and long-term Gd skin concentrations and in the propensity to induce skin lesions have been described. Interestingly, also in clinical studies similar differences between the GBCAs and the risk to induce NSF were reported (52,53).…”
Section: Discussionsupporting
confidence: 52%
“…In vivo major differences between the different GBCAs with regard to short-and long-term Gd skin concentrations and in the propensity to induce skin lesions have been described. Interestingly, also in clinical studies similar differences between the GBCAs and the risk to induce NSF were reported (52,53).…”
Section: Discussionsupporting
confidence: 52%
“…El deterioro de la función renal, tanto agudo como crónico, es considerado el mayor factor de riesgo para generar FSN [18][19][20] . No existe predilección por etiología o duración de la falla renal 21,22 .…”
Section: Función Renalunclassified
“…Se estima que pacientes con ERC en etapa 5 (filtración glomerular < 15 ml/min/1,73 m 2 ) y etapa 4 (filtración glomerular entre 15 a 29 ml/min/1,73 m 2 ) tienen entre 1% y 7% de probabilidad de desarrollar FSN posterior a una o más exposiciones a algunos MC-Gd 8,9,16,18,19,22,23 . Sólo se ha publicado un reporte de caso en el cual el paciente desarrolló FSN con valores de filtración glomerular sobre 30 ml/min/1,73 m 2 24 .…”
Section: Función Renalunclassified
“…Despite the limitations of the MDRD equation, it should be noted that the risk assessment for NSF in the literature has been largely based on eGFR assessment by the MDRD equation, with the great majority of cases occurring in patients with an eGFR <30 mL/ min/1.73 m 2 (32,33). It is of great importance to stress that the MDRD formula, which assumes a stable serum creatinine level, is not reliable in patients with acute renal failure, which is an independent risk factor for NSF (34,35).…”
Section: Mdrd Equationmentioning
confidence: 99%